Multiphase transfer model for intermittent microwave-convective drying of food: Considering shrinkage and pore evolution. (October 2017) - Joardder, Mohammad U.H.; Kumar, C.; Karim, M.A.
Highlights: Multiphase modelling of IMCD provides a better understanding of the physics. Consideration of shrinkage in model provide more realistic results. Intermittency of microwave result in uniform moisture and tempurature distribution. Abstract: Intermittent microwave convective (IMCD) drying is an advanced drying technology that improves both energy efficiency and food quality during drying. Although many experimental studies on IMCD have been conducted, there is no complete multiphase porous media model describing the physics of the process available in the literature. A multiphase porous media model considering liquid water, gases and the solid matrix of food during drying can provide in-depth understanding of IMCD process. Currently there is no IMCD model that have taken shrinkage and pore evolution during drying into consideration. In this study, first a multiphase porous media model with shrinkage (IMCD2) has been developed for IMCD. Then the model has been compared with IMCD model without shrinkage (IMCD1). Simulated temperature, moisture content, density, porosity from IMCD2 are then validated against experimental data. The profile of vapour pressures and evaporation during IMCD are also presented and discussed.